Tropical Sprue (TS); Experience in a Tertiary Care Hospital - Perveen, I; Hasan, M; Kibria, GM; Rahman, MM (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Background: Tropical sprue (TS) is a common cause of malabsorption in the tropics. No report has yet been published on TS in Bangladesh. This report aimed to describe clinical picture of TS patients in a tertiary care hospital. Methods: The data were collected from the admission and discharge registers and register of follow-up clinic of Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University during the period of 1981- 2004. Results: A total of 23 patients with a mean age of 36.42 years were diagnosed to have TS (8 females and 15 males). Mean duration of their symptoms was eight months. Important presenting features were loose motions (82.6%) and progressive weight loss (73.91. Approximately 43.47% patients presented with abdominal discomfort or pain, 26.02% with fever and 26.03% with skin changes. Mean hemoglobin and serum albumin levels were 9.71gm/dl and 31.16 gm/dl respectively. Fecal fat was positive in only eight cases. Contrast X-ray showed dilatation of small intestinal loops in four cases and flocculation of dye in two cases. Duodenal biopsy showed partial (16cases) or subtotal (four cases) villous atrophy with chronic inflammatory cell infiltrate in lamina propria in 91.3 % cases. Patients treated with tetracycline or ciprofloxacin along with folic acid showed good initial response with improvement of bowel motions, weight gain and anemia. Only two patients presented with recurrent attacks. In conclusion, TS is also prevalent in our country. A good number of TS patients presented with abdominal responses were pain and fever along with diarrhoea and weight loss. Small intestinal mucosal changes and treatment typical to TS. Key Words: Tropical sprue; clinical profile Key Message: The mal-absorptive disorder Tropical sprue is also prevalent in Bangladesh. Patients mostly presented with loose motions and progressive weight loss. A good number of TS patients’ present with abdominal pain and fever along with diarrhoea and weight loss. DOI: 10.3329/jbsp.v29i1.7166 J Bangladesh Coll Phys Surg 2011; 29:16-20